Intellectual capital dimensions and employee performance: The mediating role of organizational learning - Sawasn Al-Husseini (Cogent Business & Management, 2023)
Intellectual capital is recognized as the most important driver of economic development and the key to enhancing innovation and performance. This research seeks to examine the impact of intellectual capital (human, relational, and structural) on employee performance through the mediating role of organizational learning. The study surveyed 438 managers based in Iraqi banks. A model was developed and conditional hypotheses were tested using structural equation modeling with AMOS. The results show that the three components of intellectual capital (human, relational, and structural capital) improve employee performance and that organizational learning mediates the relationship between intellectual capital and employee performance. The research gave evidence to support the use of intellectual capital and organizational learning to enhance the performance of the employee within banking sector in developing countries, particularly Iraq.
Keywords: 650; employee performance; intellectual capital; organisational learning